2016
DOI: 10.1002/jctb.4908
|View full text |Cite
|
Sign up to set email alerts
|

Urban wastewater treatment plant provided with tertiary finishing lagoons: management and reclamation for irrigation reuse

Abstract: BACKGROUND: In recent years water scarcity has become more prominent, increasing the need for new practices in terms of efficient water management. Reuse and valorization of water from wastewater treatment plants (WWTPs) can help solve the problem. RESULTS:The traditional denitrification/nitrification scheme followed by a natural disinfection/storage tank has been studied in order to optimize the process for irrigation reuse. The study is based on data produced by an experimental pilot-scale plant, located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The model was applied to wastewater reuse scenarios to identify the benefits and problems associated with each system. A traditional denitrification/nitrification scheme followed by a natural disinfection of storage tanks was evaluated using WEST software based on data produced from a pilot-scale plant and a field campaign carried out on the internal fresh water to optimize reuse for irrigation (Fiorentino et al, 2016). The study showed that high pollutant removal efficiency and a water storage system capable to meet irrigation needs are key factors in enabling water reuse.…”
Section: Modelingmentioning
confidence: 99%
“…The model was applied to wastewater reuse scenarios to identify the benefits and problems associated with each system. A traditional denitrification/nitrification scheme followed by a natural disinfection of storage tanks was evaluated using WEST software based on data produced from a pilot-scale plant and a field campaign carried out on the internal fresh water to optimize reuse for irrigation (Fiorentino et al, 2016). The study showed that high pollutant removal efficiency and a water storage system capable to meet irrigation needs are key factors in enabling water reuse.…”
Section: Modelingmentioning
confidence: 99%
“…In this regard, Nature-based Solutions (NbS) such as constructed wetlands (CW) (Capodaglio et al, 2017;Kobayashi et al, 2020), ponds and lagoons (PL) (Rizzo et al, 2020;Fiorentino et al, 2016), green walls (GW) (Svete, 2012;Masi et al, 2016a;Fowdar et al, 2017) and green roofs (GR) (Zehnsdorf et al, 2019) have emerged as alternative "green" technologies to facilitate water reuse in cities. Besides ensuring a set of environmental and socio-economic co-benefits (for example, enhancing biodiversity, improving air quality and promoting wellbeing), these "green" technologies are also recognized for being environmentally friendly and cost-effective technologies for water treatment, mainly due to their low energy demand and low implementation and maintenance costs (Fowdar et al, 2017;Zehnsdorf et al, 2019;Kobayashi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, wastewater reclamation could become an alternative water resource. In this context, different technologies are being developing nowadays to treat urban wastewater (Gómez et al 2006;Ferro et al 2015;Fiorentino et al 2016;Gutiérrez-Alfaro et al 2018). They are designed by considering that for a safe use of this water, pathogens should be removed and two parameters are considered to be the main targets: the fecal pathogen Escherichia coli (E. coli) and the turbidity.…”
Section: Introductionmentioning
confidence: 99%